2021
DOI: 10.3389/fimmu.2021.662048
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Activity on Mesenchymal Cells Negatively Regulates OX40L to Maintain Bone Marrow Immune Homeostasis Under Stress Conditions

Abstract: BackgroundWithin the bone marrow (BM), mature T cells are maintained under homeostatic conditions to facilitate proper hematopoietic development. This homeostasis depends upon a peculiar elevated frequency of regulatory T cells (Tregs) and immune regulatory activities from BM-mesenchymal stem cells (BM-MSCs). In response to BM transplantation (BMT), the conditioning regimen exposes the BM to a dramatic induction of inflammatory cytokines and causes an unbalanced T-effector (Teff) and Treg ratio. This imbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In B cells, CD40 signaling promotes germinal center formation, immunoglobulin (Ig) isotype switching, and memory B cell survival [ 29 , 30 ]. A previous study revealed that CD40+ cells in bone marrow-derived MSCs may be a key immune regulatory element in the bone marrow [ 31 ]. Our previous study demonstrated that CD40 may be a key molecule in the immunomodulatory capacity of primed T-MSCs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In B cells, CD40 signaling promotes germinal center formation, immunoglobulin (Ig) isotype switching, and memory B cell survival [ 29 , 30 ]. A previous study revealed that CD40+ cells in bone marrow-derived MSCs may be a key immune regulatory element in the bone marrow [ 31 ]. Our previous study demonstrated that CD40 may be a key molecule in the immunomodulatory capacity of primed T-MSCs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition and treatment of GvHD may limit tissue injury and potentially restore hematopoietic function while damage is still reversible. Of particular therapeutic interest is the transfusion of immune-regulatory cells, such as MSCs or Tregs, which could theoretically restore cellular composition, as well as enhance the immune-suppressive function of the bone marrow niche [12,123]. Of note, although MSCs show efficacy in the treatment of steroid refractory GvHD, their capacity to migrate to and reconstitute the bone marrow niche remains subject of debate [124].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%